2012
DOI: 10.1007/s10812-012-9554-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear refractive index of vanadate crystals in the near IR region

Abstract: We used the single-beam Z-scan method, employing picosecond laser pulses with λ = 1064 nm, to measure the nonlinear refractive index and nonlinear absorption in vanadate crystals, which are promising for design of laser sources. We have established that there is practically no nonlinear absorption in these crystals in the near IR range and that doping them with neodymium ions leads to a significant reduction in the nonlinear refraction. This effect can be used to partially compensate for the negative impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…For CW and pulsed operation, the saturation fluence then decreases by a factor of 5 as well, enhancing the power or energy extraction efficiencies in damage-limited operation. The saturation intensity, found by dividing Equation (76) by the upper level fluorescence lifetime, decreases by the same factor of 5 as well.…”
Section: Spectroscopic and Lasing Parametersmentioning
confidence: 71%
“…For CW and pulsed operation, the saturation fluence then decreases by a factor of 5 as well, enhancing the power or energy extraction efficiencies in damage-limited operation. The saturation intensity, found by dividing Equation (76) by the upper level fluorescence lifetime, decreases by the same factor of 5 as well.…”
Section: Spectroscopic and Lasing Parametersmentioning
confidence: 71%
“…It can be shown that the semiclassical equations ( 20), ( 21), ( 25), ( 27), (30), (32) obtained from the wave equation for the field in the laser cavity are fully consistent with the equations of quantum theory of intracavity Raman conversion based on the analysis and transformation of the field + matter Hamiltonian [23]. This is achieved when in the quantum equations the frequency Stark shifts, the self-energy terms, and the quantum noise are neglected, and the operator equations are reformulated into equations for quantum-mechanical averages.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the effects of the non-resonant third-order susceptibility are not taken into account. In most Raman-active crystals providing effective Raman scattering in the near IR region, such as barium nitrate, diamond, vanadates, tungstates, molybdates, etc, the nonlinear refraction coefficients (being proportional to non-resonant third-order susceptibilities), do not exceed the value of n 2 ≈ 2 10 −15 cm 2 W −1 [30][31][32]. Accordingly, for the intracavity intensities 5 GW cm −2 that is realized very often in compact solid-state Raman lasers the corrections for refractive indices (product n 2 -intensity) are less than 10 −5 .…”
Section: Theorymentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42]). in Table 1 [35][36][37][38][39][40][41][42] . Among these, Nd:GdVO 4 is an attractive candidate for high-power lasers because of its considerably higher thermal conductivity, which endows it with an ideal combination of the merits of Nd:YVO 4 and Nd:YAG [35,43] .…”
Section: Introductionmentioning
confidence: 99%